Poetry as window and mirror : positioning the poet in Hellenistic poetry - Klooster, Jacqueline, 1976- (Leiden : Brill, 2011)
Concentrating on the interaction between contemporary Hellenistic poets, this book attempts to chart the complex dynamics of Alexandrian poetical imitation and reception in the light of poetical self-positioning.
Acknowledgements -- Texts, Translations and Conventions -- Introduction -- 1., Poetic Predecessors in Epigram -- 2., Coming to Terms with Poetic Models -- 3., Appropriating Mythical Poets -- 4., Criticizing Contemporaries -- 5., Praising Contemporaries -- 6., Persona, Alias and Alter Ego in Sphragis-Poetry -- 7., Authority and Inspiration in the Age of the Museum -- Conclusion -- Appendix, List of Hellenistic Epigrams on Poets
Obsahuje bibliografické odkazy a rejstříky
Elektronická reprodukce.
Keywords: 3. století př. Kr; řecká antická poezie -- 3. století př. Kr; řecká antická poezie -- starověký Egypt -- 3. století př. Kr; helénismus; interpretace a přijetí literárního díla; subjektivita v literatuře; realismus v literatuře; Greek ancient poetry -- 3rd century B.C.; Greek ancient poetry -- ancient Egypt -- 3rd century B.C.; hellenism; interpretation and reception of literature; subjectivity in literature; realism in literature; Alexandrie (Egypt); Alexandria (Egypt); monografie; e-knihy online; monographs; e-books online